2012
DOI: 10.3109/03014460.2012.742138
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic ancestry in the admixed Brazilian population from Rio de Janeiro using 46 autosomal ancestry-informative indel markers

Abstract: The Brazilian population is highly heterogeneous as a result of five centuries of inter-ethnic mating between native Amerindians, European colonizers and Africans arrived during slavery. This study aimed to assess the proportions of inter-ethnic admixture in the Brazilian population of Rio de Janeiro using autosomal Ancestry-Informative Markers (AIMs). The autosomal data were also compared to the results expected from uniparental genetic markers. A total of 413 individuals were genotyped for 46 AIM-Indels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 21 publications
7
47
1
7
Order By: Relevance
“…33 Recently, using a set of AIM-INDELs, we estimated the ancestry proportions of individuals from Amazonas, Belém, and Rio de Janeiro populations in Brazil. 33,37 We concluded that this panel has accuracy and is suitable to estimate genetic ancestry in highly admixed populations such as the Brazilian. 33,37 Herein, we aimed to establish the QMVR of BAT-25, BAT-26, NR-21, NR-24, and NR-27 markers, in a Brazilian healthy population, to evaluate the feasibility of MSI status determination of tumors without the need of matching normal DNA.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…33 Recently, using a set of AIM-INDELs, we estimated the ancestry proportions of individuals from Amazonas, Belém, and Rio de Janeiro populations in Brazil. 33,37 We concluded that this panel has accuracy and is suitable to estimate genetic ancestry in highly admixed populations such as the Brazilian. 33,37 Herein, we aimed to establish the QMVR of BAT-25, BAT-26, NR-21, NR-24, and NR-27 markers, in a Brazilian healthy population, to evaluate the feasibility of MSI status determination of tumors without the need of matching normal DNA.…”
Section: Introductionmentioning
confidence: 88%
“…33,37 We concluded that this panel has accuracy and is suitable to estimate genetic ancestry in highly admixed populations such as the Brazilian. 33,37 Herein, we aimed to establish the QMVR of BAT-25, BAT-26, NR-21, NR-24, and NR-27 markers, in a Brazilian healthy population, to evaluate the feasibility of MSI status determination of tumors without the need of matching normal DNA. Furthermore, we intend to determine the ancestry of Brazilian individuals using specific AIMINDELs and correlate with their QMVR.…”
Section: Introductionmentioning
confidence: 88%
“…4,5 Other studies, in contrast, have demonstrated a significant association between self-declared color/ ethnicity and genetic ancestry. [6][7][8] In the present study we evaluate the correlation between selfreported skin color and genetic ancestry, and describe the patterns of genetic structure and admixture stratification in two cities from the Northeast region of Brazil: Fortaleza, capital of the state of Ceará, and Salvador, capital of the state of Bahia. The two capitals are 1300 km apart, and have different demographic histories with respect to African slavery and European immigration.…”
Section: Introductionmentioning
confidence: 99%
“…To conduct this study, we used the highest cutoff point value of the AIMs (65%), which provided a reasonable number of individuals per ancestries groups. We believe that this cutoff value is appropriate because it is greater than the average value of the European AIMs described for Ouro Preto's population (50.3-53.9%) [18], and is the average of which is observed to southeastern Brazilian population (55.2-79.9%) [5,[22][23][24]. Although the prevalence of obesity, type 2 diabetes, and hypertension differs between ethnic groups, there are few correlation studies between genetic ancestry and risk phenotypes for these diseases.…”
Section: Discussionmentioning
confidence: 95%